2017
DOI: 10.12783/dtssehs/icss2016/8956
|View full text |Cite
|
Sign up to set email alerts
|

Organization Participation in Place Branding: From Institutional Perspective

Abstract: Abstract. Faced with increasingly fierce global competition, place branding has become an important strategic tool to obtain regional competitive advantage. As a public brand, place brand needs all organizations in the region to build participation beliefs and to achieve specific participation behavior. From the perspective of institutional theory, this paper argues that the internal driving force of organization participation in place branding derives from the regulative, normative and cultural-cognitive pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dastgerdi et al [12] found that science, creativity, and talent can enhance system innovation while ensuring urban stakeholders' legitimate rights and interests to establish a positive urban image and improve a city's reputation and sustainable development. Scholars also studied the driving factors of urban brand development from the perspective of brand value co-creation [13,14], cluster generation [15], government construction [3], system and environment [16], and marketing [17]. There have also been studies regarding the adverse factors of urban brand development from the perspective of urban crisis [18] and the relationships between urban stakeholders [19][20][21].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dastgerdi et al [12] found that science, creativity, and talent can enhance system innovation while ensuring urban stakeholders' legitimate rights and interests to establish a positive urban image and improve a city's reputation and sustainable development. Scholars also studied the driving factors of urban brand development from the perspective of brand value co-creation [13,14], cluster generation [15], government construction [3], system and environment [16], and marketing [17]. There have also been studies regarding the adverse factors of urban brand development from the perspective of urban crisis [18] and the relationships between urban stakeholders [19][20][21].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Enterprises and industries are the cornerstones of urban development. Enterprise innovation and development, industrial structure upgrading, and industrial scale advantages are conducive to forming large enterprise brands and driving industrial mechanisms to develop regional branding and strengthen city branding associations [15][16][17][18][19][20][21][22][23][24][25]. Some scholars have emphasized the role of innovation on city brands from a theoretical perspective and suggest that in the process of city brand construction, the internal strength of the brand needs to be improved with the help of innovation so that a unique city brand image can be established [26,27].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%